Bit of Barfi, Sip of Margarita: Disability and Sexuality in Hindi Films. Issue 1 (June 2018) - Jain, Jayana
The aim of this article is to analyse the representation of disability and sexuality in selected Hindi films. The study compares the sexual construct of the disabled bodies of Jhilmil in Anurag Basu's Barfi! (2012) and Laila in Shonali Bose's Margarita with a Straw (2014). On the one hand, if the ambivalent representation of the disabled and sexualized body of Jhilmil seems to reinforce the ableist and heterosexual ethos, the disabled and queered body of Laila indicates possibilities, resistance and interruptions. In a larger context, it proposes to indicate a much-needed framework to engage with the politics of representation of disability and sexuality in gender and Hindi film studies.